Efficacy and Safety of Nicotine Replacement Therapy in Intensive Care Units: A Systematic Review (Asian Journal of Pharmaceutics (AJP), 2024)
Nicotine replacement therapy (NRT) is a potential intervention for managing nicotine withdrawal symptoms incritically ill patients in the intensive care unit (ICU). This systematic review evaluated the effectiveness and safetyof NRT in adult ICU patients with a history of nicotine dependence or tobacco use. A comprehensive literaturesearch was conducted from January 31, 2010, to September 31, 2024, using the PubMed, Scopus, and Web ofScience databases. Eight studies that assessed the impact of NRT on nicotine withdrawal symptoms, ICU stayduration, delirium incidence, mortality, and adverse events were included in the review. These results suggestthat NRT may be effective in reducing nicotine withdrawal symptoms in patients in the ICU. However, evidenceregarding its impact on ICU outcomes, such as length of stay and delirium incidence, is inconclusive. Some studiesreported potential adverse effects, including increased agitation and delirium, whereas others found no significantincrease in adverse events. The safety profile of NRT in the ICU setting remains controversial, and further, highqualityrandomized controlled trials are required to establish its efficacy and safety in critically ill patients. Thisreview highlights the importance of individualized patient management and the needs for a balanced approachwhen incorporating NRT into ICU care, considering factors such as nicotine dependence severity, cardiovascularhealth, and the overall clinical profile. Future research should focus on optimizing NRT use in the ICU, exploringoptimal formulations and dosages, and investigating the potential interactions with common ICU medications.